Deep anterior lamellar keratoplasty in the management of keratoconus - Rajesh Fogla (Indian Journal of Ophthalmology, 2013)
Advanced cases of keratoconus often require surgical intervention to restore corneal anatomy and improve eyesight. Penetrating keratoplasty (PK) although commonly performed has potential risk of immunological rejection and is now no longer automatically the first choice of surgery. DALK procedures have evolved, which allows surgical replacement of recipient′s corneal stroma, leaving behind healthy descemet membrane (DM) and endothelium. This reduces the risk of allograft endothelial rejection and late graft failure. In recent times, DALK techniques have led to significant improvements in visual outcome and current results are comparable to PK. Big bubble technique of DALK has become the most popular among the various surgical techniques described. Manual near DM DALK also gives good outcome although the visual recovery is often delayed. Future integration of femtosecond laser technology along with diagnostic imaging technology is likely to further improve outcomes of DALK in keratoconus.